Unveiling the prenatal features of HADDS: A case report and literature review - Lina Hu; Dongzhi Li; Li Zhen; Yanan Wang (Heliyon)
Hypotonia, Ataxia, and Delayed Development Syndrome (HADDS), triggered by EBF3 mutations, is a neurodevelopmental disorder syndrome characterized by hypotonia, ataxia, and developmental delay. The affected individuals often are unable to care for themselves, which has a significant impact on society and families. Hence, prenatal screening and diagnosis are particularly important. However, symptoms and signs of HADDS caused by mutations in EBF3 have not been studied until now. Herein, we report the case of a 1-year-old boy carrying a heterozygous point mutation in the EBF3 gene (c.271 del, p. Asp91Thrfs∗41), who had typical signs and symptoms of mental retardation, hypotonia, developmental delay, neurogenic bladder, constipation, and Pectus excavatum, in addition to atypical facial features. HADDS was diagnosed by Whole Exome Sequencing on a family trio (Trio-WES) for recurrent urinary tract infection with dysuria at 6 months of age, with a normal karyotype and chromosomal microarray analysis (CMA). The variant is a de novo shifted code mutation, which expands the pathogenic gene spectrum of EBF3. Furthermore, we did a retrospective analysis of HADDS patients with a history of pregnancy and childbirth. We emphasized that reduced fetal movement, systematic ultrasound scanning, and fetal MRI might add evidence for prenatal diagnosis. The study is the first to explore prenatal screening for this EBF3 gene-related HADDS and is of great relevance.